PPARγ Mediates the Cardioprotective Roles of Danlou Tablet After Acute Myocardial Ischemia-Reperfusion Injury - Wei, Meng; Guo, Mengying; Meng, Xinxiu; Li, Lin; Wang, Hongyun; Zhang, Mingxue; Bei, Yihua (Frontiers in Cardiovascular Medicine, 2022)
Ischemic heart disease is one of the biggest threats to human life in the world. Reperfusion therapy is an effective strategy to reduce infarct size and ischemic injury. However, reperfusion process may cause secondary myocardial injury which is defined as ischemia-reperfusion injury (IRI). Exploring potential therapeutic strategy to attenuate IRI is extremely important. Danlou tablet (Dan), a Chinese herbal compound consisting of ten herbs, has been identified to be protective for the heart. However, the mechanism of Dan-induced cardioprotection after acute reperfusion was unelucidated. In this study, to investigate the role and mechanism of Dan in myocardial IRI, we performed acute IRI modeling in mice and oxygen-glucose deprivation–reperfusion (OGD/R)-induced apoptosis in primary neonatal rat cardiomyocytes (NRCMs). We found that Dan had protective effect against acute IRI in mice, as evidenced by reduced infarct size, TUNEL-positive cardiomyocytes (CMs), and Bax/Bcl2 ratio and cleaved-caspase 3/caspase 3 ratio in vivo. Meanwhile, Dan inhibited OGD/R-induced apoptosis of NRCMs in vitro. Mechanistically, Dan could activate proliferator-activated receptor gamma (PPARγ) in both IRI hearts and OGD/R-stressed NRCMs, while inhibition of PPARγ attenuated the protective effect of Dan against IRI in vivo and OGD/R-induced CM apoptosis in vitro. These data reveal that Dan attenuates acute myocardial IRI and CM apoptosis through activating PPARγ. Our findings may extend the knowledge of Chinese medicine and provide potential strategy for the precise treatment of ischemic heart diseases.